THE CURRENT STATE OF DEVELOPMENT OF RESTAURANT BUSINESS IN THE ZHYTOMYR REGION - ZAPOTOTSKYI, Sergii-; TYSHCHENKO, Svitlana (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2025)
Background. The restaurant services market has entered a new stage of development due to the events that have taken place in our country and the world: COVID-19 and modern military aggression, which have led to the emergence of new formats of restaurant business establishments. The activity of restaurant business establishments during the COVID-19 period contributed to the introduction of new modern IT technologies in the field of catering, and the development of new methodological recommendations for the operation of establishments in special covid conditions.Methods. In writing the paper, we used such methods as analysis, synthesis, observation and comparison to identify the patterns of functioning of restaurant business establishments.Results. The study of the current state of activity of restaurant business establishments both in the country as a whole and in the city of Zhytomyr in the conditions of hostilities has shown that modern restaurant business services provide not only basic but also higher needs of society. The following trends in the restaurant business are becoming popular: food markets and innovative food courts (cultivation of markets and their transformation into universal gastronomic spaces); slow-food (slow consumption of tasty and healthy food, education of taste in customers and restoration of their respect for food); finger-food (buffet where you eat only with your hands) and tapas (one huge plate for everyone); transition to cooking with environmentally friendly products, etc. It is established that the level of development of the restaurant business in the country is different and needs to be improved. The specific problems faced by restaurateur entrepreneurs in relocating their establishments to safer areas are identified. An analysis of the current state of development of restaurant business establishments in the city of Zhytomyr is carried out.Conclusions. The main directions of activity that can help to restore the work of restaurant business establishments in the territories that have suffered enormous destruction are proposed. The advanced directions of the world market, which can be used by restaurant business establishments of Ukraine and the main European popular trends, are studied. The food culture is being modernised, with much borrowed from the European food culture. Various formats of restaurant business establishments are proposed, which are proven, standardised forms of organisation of production and sale of catering products. The directions for improving the restaurant business through the use of innovative approaches that exist in the field of service in the world restaurant business are investigated.
Keywords: restaurant business; restaurant formats; restaurant business trends; innovations; competition